Pharmacovigilance in hospice/palliative care: net effect of gabapentin for neuropathic pain. Issue 3 (16th October 2014) - Sanderson, Christine; Quinn, Stephen J; Agar, Meera; Chye, Richard; Clark, Katherine; Doogue, Matthew; Fazekas, Belinda; Lee, Jessica; Lovell, Melanie R; Rowett, Debra; Spruyt, Odette; Currow, David C
Abstract : Objective: Hospice/palliative care patients may differ from better studied populations, and data from other populations cannot necessarily be extrapolated into hospice/palliative care clinical practice. Pharmacovigilance studies provide opportunities to understand the harms and benefits of medications in routine practice. Gabapentin, a γ-amino butyric acid analogue antiepileptic drug, is commonly prescribed for neuropathic pain in hospice/palliative care. Most of the evidence however relates to non-malignant, chronic pain syndromes (diabetic neuropathy, postherpetic neuralgia, central pain syndromes, fibromyalgia). The aim of this study was to quantify the immediate and short-term clinical benefits and harms of gabapentin in routine hospice/palliative care practice. Design: Multisite, prospective, consecutive cohort. Population: 127 patients, 114 of whom had cancer, who started gabapentin for neuropathic pain as part of routine clinical care. Settings: 42 centres from seven countries. Data were collected at three time points—at baseline, at day 7 (and at any time; immediate and short-term harms) and at day 21 (clinical benefits). Results: At day 21, the average dose of gabapentin for those still using it (n=68) was 653 mg/24 h (range 0–1800 mg) and 54 (42%) reported benefits, of whom 7 (6%) experienced complete pain resolution. Harms were reported in 39/127 (30%) patients at day 7, the most frequent of which were cognitive disturbance, somnolence, nausea and dizziness. Ten patients had their medication ceased due to harms. The presence of significant comorbidities, higher dose and increasing age increased the likelihood of harm. Conclusions: Overall, 42% of people experienced benefit at a level that resulted in continued use at 21 days.